Evaluation Of Regional Economic Performance, Local Government Financial Performance, And Public Service Performance In The New Autonomous Region - Dewi Puspitasari; Yusuf Kurnia Yuga Sudana (Cita Konsultindo Research Center, 2023)
After the enactment of Government Regulation No. 78 of 2007, regional autonomy has raised pro and contra attitudes among politicians, leaders, the public, government officials and among experts who debate the benefits or disadvantages arising from the many areas that are divided. The purpose of this study was to analyze the impact of regional autonomy using the approach of regional economic performance, local government financial performance, and public service performance in Pesawaran Regency, West Bandung Regency, Kubu Raya Regency, North Konawe Regency, Mamberamo Raya Regency, and East Manggarai Regency with main area. This research method uses descriptive quantitative with the treatment–control method to evaluate the performance and conditions of the new autonomous regions. The research data was processed using indexation and ratio methods. The results of the study concluded that the performance of the new autonomous regions is still not as high as the parent regions. So it is necessary to evaluate the regional autonomy policy.